DOPING REGULATIONS IN INTERNATIONAL SPORT (KONFERENSIYA, 2025)
This article examines the global regulatory framework designed to combat doping in modern sports. As athletic performance reaches unprecedented levels, the use of performance-enhancing substances has become a major threat to fair competition. The study explores the historical evolution of anti-doping efforts, the structure of the World Anti-Doping Agency (WADA), implementation of the World Anti-Doping Code, and the disciplinary mechanisms used to ensure compliance. The paper also analyzes testing procedures, athlete rights, doping technologies, and ethical challenges faced by international sport organizations. Findings show that a strong, transparent, and science-based anti-doping system is essential for protecting athlete health, maintaining integrity, and preserving trust in global sport